2021
DOI: 10.3389/fneur.2021.650024
|View full text |Cite
|
Sign up to set email alerts
|

Assessment Methods of Post-stroke Gait: A Scoping Review of Technology-Driven Approaches to Gait Characterization and Analysis

Abstract: Background: Gait dysfunction or impairment is considered one of the most common and devastating physiological consequences of stroke, and achieving optimal gait is a key goal for stroke victims with gait disability along with their clinical teams. Many researchers have explored post stroke gait, including assessment tools and techniques, key gait parameters and significance on functional recovery, as well as data mining, modeling and analyses methods.Research Question: This study aimed to review and summarize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 176 publications
1
43
0
Order By: Relevance
“…In recent years, several studies have demonstrated that portable devices, such as electromygraphy, insole foot pressure sensors, motion capture systems, and inertial measurement units (IMUS), can objectively measure gait and be used to compute gait features [ 18 , 19 , 20 , 21 , 22 , 23 ]. Of all of these devices, IMUs might be the most feasible for clinical use because measuring with IMUs requires no expensive equipment, and they are easy to operate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, several studies have demonstrated that portable devices, such as electromygraphy, insole foot pressure sensors, motion capture systems, and inertial measurement units (IMUS), can objectively measure gait and be used to compute gait features [ 18 , 19 , 20 , 21 , 22 , 23 ]. Of all of these devices, IMUs might be the most feasible for clinical use because measuring with IMUs requires no expensive equipment, and they are easy to operate.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that IMUs can be used to monitor gait recovery; hence, they function as a clinical evaluation tool. Despite the advantages of using IMUs to assess gait, regular IMU-based measurements have yet to be adopted by clinicians [ 21 , 29 ]. This is because IMU data needs to be collected, processed, and converted to clinically relevant information, requiring time, processing tools, and expertise.…”
Section: Introductionmentioning
confidence: 99%
“…However, 3DGA is rather costly, and the related measurements provide a large body of data to be interpreted, which may be inconvenient in the clinical setting. Due to these drawbacks, many researchers worldwide are looking for new solutions specifically enabling gait analysis in patients after stroke (Ferrarello et al, 2013;Begg et al, 2014;Solanki and Lahiri, 2018;Li et al, 2019;Tian et al, 2019;Seo et al, 2020;Iosa et al, 2021;Mohan et al, 2021;Wang et al, 2021). As an example, Seo et al proposed an assessment method referred to as clinometric gait analysis and applying a smart insoles technology.…”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of our knowledge, there is no consensus regarding the method and its suitability for assessing gait interlimb coordination in poststroke patients [31].…”
Section: Introductionmentioning
confidence: 99%